1998
DOI: 10.1136/bjo.82.7.797
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of ocular surface epithelium barrier function in patients with atopic dermatitis

Abstract: Aims-To assess the integrity of the ocular surface epithelium in patients with atopic dermatitis from the viewpoint of its barrier function. Methods-49 patients with atopic dermatitis with blepharoconjunctivitis (ABC group), 27 age matched patients with seasonal or perennial allergic conjunctivitis (AC group), and 20 volunteers with normal healthy eyes (NH group) were assigned to this study. Ocular surface epithelium barrier function was evaluated by the fluorophotometric method using a slit lamp fluorophotome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 12 publications
(8 reference statements)
2
25
0
2
Order By: Relevance
“…Yokoi evaluated corneal epithelial barrier function in patients with atopic dermatitis and atopic blepharoconjunctivitis by measurement of fluorescein uptake using fluorescence photometry. 58 They found that this barrier was impaired in patients with atopic dermatitis and suggested several mechanisms that altered corneal epithelial permeability. Among them, eosinophil cationic protein, such as MBP and ECP, in the tear fluid are potential candidates, because these proteins have been demonstrated to have a cytotoxic effect on corneal epithelial cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Yokoi evaluated corneal epithelial barrier function in patients with atopic dermatitis and atopic blepharoconjunctivitis by measurement of fluorescein uptake using fluorescence photometry. 58 They found that this barrier was impaired in patients with atopic dermatitis and suggested several mechanisms that altered corneal epithelial permeability. Among them, eosinophil cationic protein, such as MBP and ECP, in the tear fluid are potential candidates, because these proteins have been demonstrated to have a cytotoxic effect on corneal epithelial cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…For example, allergy-associated substances derived from eosinophils have been shown in tears and have been shown to have cytotoxic effects on corneal epithelial cells in vitro. 36 An impaired ocular surface epithelial barrier has been shown in patients with atopic dermatitis and mild blepharoconjunctivitis without keratopathy. 36 This impairment was not evident in control subjects with seasonal or perennial allergic conjunctivitis 36 and may increase susceptibility to trauma from abnormal rubbing.…”
Section: Increased Susceptibility To Rubbing Traumamentioning
confidence: 99%
“…24 A family history of atopy is an important factor but the diagnosis is sometimes based on unspecified criteria. [26][27] In other cases an atopic family history diagnosis includes the specific criterion of atopic disease being present in a first-degree relati~e.~,*~ Even so, this criterion is dependent on an accurate diagnosis for the first degree relative. In addition, the lack of control samples in some studies may explain some of the conflicting evidence for an association between keratoconus and atopy.…”
Section: Keratoconus and Eye-rubbing Mcmonnies And Bonehammentioning
confidence: 99%